Global cloud properties on Venus from orbital infrared spectroscopy - Barstow, J; Joanna Katy Barstow (2012)
This thesis describes the derivation of Venusian global cloud properties from infrared remote sensing data obtained by the Visible and Infrared Thermal Imaging Spectrometer (VIRTIS) on the European Space Agency Venus Express satellite. A computationally-efficient retrieval method is designed to exploit the dataset, which provides coverage of the entire nightside southern hemisphere of Venus. Spatially-resolved near-infrared spectra have been used to derive improved models of the vertical structure and global distribution of cloud properties in the southern hemisphere. Wavelengths within transparency windows in the 1.0 - 2.6 micron range covered by VIRTIS are sensitive on the nightside to absorption by the lower and middle sulphuric acid cloud layers, which are back-lit by thermally-emitted radiation from the hot lower atmosphere (Taylor et al. 1997). The cloud model used to interpret the spectra builds on work by Crisp (1986), Pollack et al. (1993) and Grinspoon et al. (1993). Retrieved parameters are the acid concentration in the cloud droplets, the average size of the particles in the lower cloud and the altitude of the cloud base in the model. Values are estimated initially using wavelength pairs selected for their unique sensitivity to each parameter, and then validated using model spectra generated using the NEMESIS radiative transfer and retrieval code (Irwin et al. 2008) as developed for Venus (Tsang et al. 2008a). The spatial variation of sulphuric acid concentration in the cloud particles is estimated ; the concentration is found to be higher in regions of optically thick cloud. The retrieved cloud base altitude varies with latitude, reaching a maximum height near -50 degreees before falling by several km towards the pole. An increase in average particle size near the pole (Wilson et al. 2008) and the finding of latitudinally-variable CO abundance at 35 - 40 km altitude (Tsang et al. 2008) are both confirmed. A decrease in tropospheric H₂O abundance at high latitudes is observed, and provides evidence for strong downwelling between +/-60 and +/-75 degrees latitude, which marks the poleward extent of the Hadley cell circulation. Long-term secular change is also observed over a period of two Earth years. The measurements presented here provide a reference dataset for microphysical and dynamical modelling of the cloud deck, and the role of the cloud as a dynamical and chemical tracer means that such observations are of considerable value for increased understanding of the Venusian atmosphere.